Inhibitory Effects of Trifluoperazine on Peripheral Proinflammatory Cytokine Expression and Hypothalamic Microglia Activation in Obese Mice Induced by Chronic Feeding With High-Fat-Diet - Huang, Hui-Ting; Chen, Pei-Chun; Chen, Po-See; Chiu, Wen-Tai; Kuo, Yu-Min; Tzeng, Shun-Fen (Frontiers in Cellular Neuroscience, 2021)
Microglia and astrocytes are the glia cells of the central nervous system (CNS) to support neurodevelopment and neuronal function. Yet, their activation in association with CNS inflammation is involved in the initiation and progression of neurological disorders. Mild inflammation in the periphery and glial activation called gliosis in the hypothalamic region, arcuate nucleus (ARC), are generally observed in the obese individuals and animal models. Thus, reduction in peripheral and central inflammation is considered as a strategy to lessen the abnormality of obesity-associated metabolic indices. In this study, we reported that acute peripheral challenge by inflammagen lipopolysaccharide (LPS) upregulated the expression of hypothalamic dopamine type 2 receptor (D2R) mRNA, and chronic feeding by high fat diet (HFD) significantly caused an increased levels of D2R in the ARC. The in vitro and in vivo studies indicated that a FDA-approved antipsychotic drug named trifluoperazine (TFP), a D2R inhibitor, was able to suppress LPS-stimulated activation of microglia and effectively inhibited LPS-induced peripheral inflammation, as well as hypothalamic inflammation. Further findings showed daily peripheral administration intraperitoneally (i.p.) by TFP for 4 weeks was able to reduce the levels of plasma tumor necrosis factor- (TNF-) and interleukin-1 (IL-1) in accompany with lower levels of plasma glucose and insulin in obese mice receiving HFD for 16 weeks when compared those in obese mice without TFP treatment. In parallel, the activation of microglia and astrocytes in the ARC was also inhibited by peripheral administration by TFP. According to our results, TFP has the ability to suppress HFD-induced ARC gliosis and inflammation in the hypothalamus.